(untitled) (CIPEEX, 2022)
INTRODUCTION: HUMAN HEALTH IS A PROMINENT ISSUE IN THE CURRENT CONTEXT OF HEALTH. MEN GENERALLY ARE NOT IN THE HABIT OF LOOKING FOR BASIC HEALTH UNITS FOR DISEASE PREVENTION AND THIS RESULTS IN THE SEARCH FOR EMERGENCY AND EMERGENCY SERVICES WHEN THE PATHOLOGY IS ALREADY INSTALLED, INCREASING THE RISK OF SEVERE AND / OR FATAL ILLNESS. OBJECTIVE: TO ANALYZE THE ADHERENCE OF ACADEMICS FROM A UNIVERSITY CENTER TO HEALTH CARE OR TREATMENT. METHOD: DESCRIPTIVE STUDY OF A QUALITATIVE APPROACH. TWENTY MALE STUDENTS, SELECTED FOR CONVENIENCE AT A UNIVERSITY CENTER IN THE STATE OF GOIS, PARTICIPATED IN THE STUDY. THE DATA COLLECTION TECHNIQUE WAS THE WRITTEN SEMI-STRUCTURED INTERVIEW. FOR DATA ANALYSIS, THE CONTENT ANALYSIS TECHNIQUE WAS ADOPTED (BARDIN, 2011). RESULTS: TWO CATEGORIES WERE FOUND: SEARCH AND ADHERENCE TO HEALTH CARE SERVICES, WHICH INCLUDES THE SEARCH OF MALE UNIVERSITY STUDENTS BY HEALTH SERVICES. THROUGH THESE CATEGORIES OF ANALYSIS, IT IS POSSIBLE TO INFER THE DELAY AND RESISTANCE TO SEEKING SUCH SERVICES SUCH AS ACCESS DIFFICULTIES AND HEALTH CARE. IT WAS ALSO FOUND THE LACK OF KNOWLEDGE ABOUT THE PNAISH, WHICH PRESENTS EXTERNAL AND INTERNAL FACTORS ASSOCIATED WITH THE DIFFICULTIES AND LACK OF ADHERENCE OF THE PARTICIPANTS TO HEALTH CARE. IT IS NECESSARY TO EMPHASIZE THE INTERNAL RESISTANCES THAT PREVENT THEM FROM SEEKING SUCH SERVICES, A PHENOMENON COMPLICATED BY THE LOW AVAILABILITY OF HEALTH SERVICES OF THIS NATURE. IT HAS BEEN FOUND THAT MEN RARELY SEEK THE HEALTH SERVICE AND WHEN THEY DO SO IT IS FOR THE TREATMENT OF INSTALLED CONDITIONS SUCH AS FLU, TONSILLITIS, EPIGASTRALGIA, HYPERTENSION, HYPERLIPIDEMIA OR OPHTHALMOLOGICAL PROBLEMS. THE DESIRE TO DO ROUTINE CHECKUPS AND CHECKUPS ALSO LEADS TO THIS DEMAND. IT IS OBSERVED THAT CURATIVE PERSPECTIVE STANDS OUT FOR THE PROMOTION OF HEALTH. OBSTACLES TO SEEKING AND ADHERING TO HEALTH CARE ARE RELATED TO LACK OF TIME, TO CULTURAL FACTORS, SUCH AS THE SHAME OF BEING FRAGILE IN THE FACE OF ILLNESS. MOST OF THEM ARE UNAWARE OF THE AVAILABILITY AND ORGANIZATION OF HUMAN HEALTH CARE IN THE COUNTRY, OR EVEN KNOW OF THE EXISTENCE OF PNAISH. CONCLUSION: THERE IS A NEED TO CREATE EFFECTIVE STRATEGIES TO RAISE AWARENESS AMONG MEN ABOUT THE IMPORTANCE OF PROMOTING THEIR OWN HEALTH, AS WELL AS FACILITATING THEIR ENGAGEMENT IN THE HEALTH CARE NETWORK, LINKING INSTITUTIONS AND PREPARING FOR SELF-CARE. THE PRESENT STUDY FOUND DATA THAT CORROBORATE WITH SEVERAL OTHER STUDIES IN THE AREA, POINTING OUT NEW PROBLEMS TO BE INVESTIGATED. INSTIGATING THE REFLECTION AND SEARCH FOR SOLUTIONS FOR HUMAN HEALTH, ESPECIALLY THOSE FOCUSED ON THE AWARENESS AND PARTICIPATION OF THE MALE POPULATION IN PROGRAMS TO PROMOTE HEALTH AND QUALITY OF LIFE.